1985
DOI: 10.1007/bf00607910
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels and myocardial content of verapamil, norverapamil and two N-dealkyl-metabolites in man

Abstract: The plasma levels and myocardial content of verapamil and its metabolites norverapamil, N-dealkylverapamil and N-dealkylnorverapamil were determined in 15 patients with valvular [3] or ischaemic [12] heart disease. The mean myocardial plasma concentration ratio (M/P) was 7.05 for verapamil, 11.45 for norverapamil, 8.93 for N-dealkylverapamil, and 11.33 for N-dealkylnorverapamil, with great interpatient variability. The highest M/P ratios of verapamil were generally found in patients with the lowest plasma leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The recent studies of Padrini et al (1985) on verapamil concentration in plasma and myocardium in patients undergoing cardiac surgery shed further light on the 'hysteresis' effect. It was found that mean M : P ratios for verapamil were approximately 7: 1 (comparable to the results of Keefe & Kates 1982).…”
Section: Uptake Of Verapamilmentioning
confidence: 97%
“…The recent studies of Padrini et al (1985) on verapamil concentration in plasma and myocardium in patients undergoing cardiac surgery shed further light on the 'hysteresis' effect. It was found that mean M : P ratios for verapamil were approximately 7: 1 (comparable to the results of Keefe & Kates 1982).…”
Section: Uptake Of Verapamilmentioning
confidence: 97%
“…According to data published by Padrini et al the mean myocardial plasma concentration ratio for verapamil was 7.05 with high inter-individual variability (range: 1.8-17.8). The ratio averaged 11.5 for norverapamil (range: 1.9-28), 8.93 for N-dealkylverapamil (range: 2.03-14.6) and 11.3 for N-dealkylnorverapamil (range: 0.87-23.9) [113]. Also, the relationship between plasma perhexiline concentrations and its uptake into the myocardium was explored by Drury et al [114].…”
Section: Cardiac Pharmaceutical Agentsmentioning
confidence: 99%
“…It was considered to be a coronary vasodilator therefore its use started as an antianginal agent in 1962 in Germany [144]. The therapeutic plasma concentration of free verapamil (not bound to proteins) in humans is between 20-800 nM [145], although the mean myocardial to plasma concentration ratio was approximately seven suggesting accumulation of the drug in the heart [146]. Indeed, verapamil can accumulate in canine myocardium in a chamber specific manner showing greater accumulation in the ventricles compared to the atria without having left versus right-sided specific distribution [147].…”
Section: Phenylalkylaminesmentioning
confidence: 99%